Recollecting Resonances : Indonesian-Dutch Musical Encounters - Bogaerts, Els (Southeast Asia Mediated, 2014)
Over time Dutch and Indonesian musicians have inspired each other and they continue to do so. Recollecting Resonances offers a way of studying these musical encounters and a mutual heritage one today still can listen to.